Sylvia Wynter: Science Studies and Posthumanism as Praxes of Being Human. (June 2020) - Adams, Jennifer D.; Weinstein, Matthew
Through dialogue, this article explores the works of Sylvia Wynter to elicit some implications for science studies. In particular, we explore her analysis of the ideological construction of Man as the paradigm for humanity and how this structures the Othering or exclusion of non-White-cis-straight-men from the definition of human in the extant Western Colonial period. We also explore the ways such ideologies find expression in the logics of some central work of science studies. We discuss the ways her oeuvre articulates with science studies, especially research conducted from a postcolonial frame, especially in her notion of a "new science" or scientia. The article also explores her notion of the "pieza, " the standardized black body of the slave trade, in relation to theories of objectivity and objectification. Finally, the dialogue considers the need to start with the writing, thinking, and scholarship of those writing from positions of exclusion, in struggle for liberation, and freedom, to recover the human within science studies.